Addendum to MANFRED R. ULITZKA (2019) Five new species of Rohrthrips (Thysanoptera: Rohrthripidae) from Burmese amber, and the evolution of Tubulifera wings. Zootaxa, 4585: 027–040. - Ulitzka, Manfred R. (Zootaxa, 2019)
Concerning the description of Rohrthrips patrickmuelleri Ulitzka (2019), it has been brought to my attention that the depositary and serial number of the holotype was not given. This information is given below in order to comply with ICZN, Article 16.4.2 (1999).